Verdade, prova e processo : esboço de uma teoria da construção da "verdade" no processo civil brasileiro - Machado, Vitor Gonçalves (2015)
The “truth” in the Brazilian civil procedure has not aroused the attention of the legal experts, not being the object of a genuine interdisciplinary research. It is necessary, in this work, understand how the “truth” will be constructed in the process so that there is a final decision more “fair” and that will prevail in the legal system. The question “what is truth” has an intrinsic focus of philosophical discussions, but the term “truth” should be previously analyzed in the field of Philosophy. Jürgen Habermas teaches that “truth” is the result that is reached through consensus among the subjects in a given time, in an open and comprehensive dialogue with a view to seeking a rational mutual understanding. Among the civil and criminal procedural experts, there is varied insights into how it should be understood the “truth”, but none can succeed in the analysis that should guide the construction of the “truth” in the process. In the intrinsic relationship between proof and “truth”, it is understood that proof should be explained in a new perspective, within a dialectical and argumentative aspect. The proof is a statement language that results of the interpretation of man on the fact that, in the civil proceedings, it shall be constructed by a rational and discursive procedure, within a context where we can see debate, argument, consensus, speech and, mainly, the adversarial principle. The adversarial principle figure as a key tool to construct the “truth” in civil procedure and should be considered broadly. Regarding the participation of procedural subjects, it is understood that must be recognized to the civil judge a greater instructive power, because it is the judge´s duty to judge, and judge is know both the law and the fact. Regarding the parties and their lawyers, it appears that lawyers are seeking the interests of its customers, but it cannot invariably conclude that they do not have the truth claim. As part of the Superior Courts, we found several positions on which “truth” should be reflected in civil proceedings. The dichotomy “formal truth” versus “real truth” and the problem of “adjectival truths” are imbroglios to be overcome by the interpreters of the law and must be overcome the terms usually used by legal experts. In fact, many problems present in the law are linguistic. Interesting legal texts in the new Brazilian Civil Procedure Code bring affirmations of ideas that we can connect them to the Habermas´ discursive theory of truth, as the primacy by consensual search of disputes from the cooperation between subjects. In the judicial process, especially in the Brazilian civil procedure modernly understood, the “truth” must be analyzed without adjectives. “Truth” is a relationship between languages. But it should not be just a game of words. The procedure to guide the construction of the “truth” in the process is essential and there must be a real consensus and mutual adoption of perspectives with respect to the vision of the parties involved, where must be present cooperation and dialogue with the goal to reconstruct facts and interpretations in a way more consensual as possible, wich takes into account the respect of the rules valid for the case at trial.